The Wayang Performance of Enthus Susmono: A Resistance of Tegal-Pesisiran Identity in Breaking the Tradition Hegemony - Hariyanto Hariyanto (Institut Seni Indonesia Yogyakarta, 2018)
AbstractThis article aims to reveal and explain the process of cultural resistance appeared as a result of cultural violence conducted by authoritarian government regime in Indonesia. The standardization process of puppetry style, which was based on the tradition hegemony of Keraton Surakarta and Ngayogyakarta, in Enthus Susmono’s view, was considered as being a political practice of cultural violence existed during the New Order era – a practice that seemed to eliminate minor puppetry traditions in the Javanese culture. It is in the framework of Titon’s model that the appearance of a culture form may result from a historical memory that this article tries to explain the cultural resistance efforts by Susmono, which were represented in his performance of Wayang golek Gagrag Tegalan, in order to articulate the cultural identity of Tegal-Pesisiran.Keywords: Enthus Susmono; wayang golek Tegal; wayang PesisiranAbstrakWayang Gaya Enthus Susmono: Resistensi Identitas Tegal-Pesisiran dalam Mendobrak Hegemoni Tradisi. Tulisan ini ingin mengungkap serta menjelaskan proses resistensi kultural yang timbul akibat praktik kekerasan budaya oleh hegemoni rezim pemerintahan yang otoriter di Indonesia. Upaya standarisasi pedalangan yang berpijak pada hegemoni tradisi dua istana, yaitu Surakarta dan Ngayogyakarta, oleh Enthus Susmono dipandang sebagai praktik politik kekerasan budaya terjadi semasa Orde Baru, yang seolah-olah menghilangkan berbagai tradisi kecil dunia pedalangan di Jawa. Melalui Pandangan Titon bahwa kemunculan sebuah bentuk kebudayaan yang didasari oleh memori kesejarahan, artikel ini menjelaskan mengenai resistensi kultural yang dilakukan Enthus Susmono, yakni melalui karyanya dalam pertunjukan Wayang Golek Gagrag Tegalan, untuk mengekspresikan dan mengartikulasikan identitas budaya Tegal-Pesisiran.Kata kunci: Enthus Susmono; wayang golek Tegal; wayang Pesisiran